An assessment, with nice guidelines as a benchmark, of delay to care in a cohort of colorectal cancer patients seen in the Witwatersrand university academic complex - Singh, Kimisha (My University, 2022)
Background Colorectal cancer (CRC) in South Africa is the second most common in women and the third in men. According to GLOBOCAN data CRC is the second most deadly cancer worldwide. As a subset, colon cancer is the fifth most deadly with an estimated 551 000 deaths in 2018. CRC makes up 5.8% of all cancer related deaths globally. Despite this, there are no screening programmes in South Africa, diagnosis of this cancer being largely dependent on symptomatic presentation. Additionally, there is no clear understanding of the significance to outcome imposed by delay to referral and delay to treatment. Unlike countries in Europe, South Africa has no guidelines defining cut-offs for acceptable delays in this context. This belies a paucity of research done around the pathways to care in this setting. Objectives To determine extent of delays to referral and treatment of CRC patients by benchmarking these timelines against the NHS two-week-rule and the European provision of no more than one month to treatment. Evaluate the variables that impact 90-day mortality post therapeutic surgery and define the significance of the delays against the identified confounders. Methods A retrospective study was done on the delay to referral, diagnosis and treatment of CRC patients. The outcome measure used was 90-day mortality post definitive treatment. A cohort of patients who presented to Witwatersrand Academic Hospitals was studied. Data from MRC CRECSA study for colorectal cancer was studied. Patients in which surgery was the primary treatment were assessed. Delays in these patients were benchmarked against fourteen days from primary contact to consultation with a treating specialist and consultation to treatment delay of more than 31 days. Further, definitive treatment delay was defined as time from referral to treatment centre and tumour resection. This was benchmarked against a cut-off of 62 days. Outcomes were then evaluated by defining the 90-day mortality in each group. Results The median referral delay was 78 days and for treatment delay was 54 days in 587 patients. Definite treatment delay median was 175 days. Of the 587 patients analysed, 341 had therapeutic surgery, of which 17 demised within 90 days post-surgery. Longer delays and higher mortality rates were seen in the public sector and lower socio-economic group of patients. Conclusion Delay in referral and treatment of colorectal cancer patients in South Africa does not meet the goals of the European time parameters set out. There were greater delays seen in patients with a lower socio economic background and in those attending the public sector. The effect of delays on 90-day mortality is doubtful. Delays to care both outside of hospitals and in hospitals may be a point of investigating in future studies. The complexity of the circumstance that gives rise to poor outcomes is highlighted by the effect of socio-economic status on 90-day mortality. This further suggests poor outcome is not driven by delay to referral or delay to treatment.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022